PENGARUH MINAT TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII UPT SMP NEGERI 1 BATANG KAPAS - Vania Frasetya (Jurnal Edukasi dan Penelitian Matematika, 2020)
The study was intended to determine how interest was affected by the result of studying the mathematics of class VII students performed in UPT SMP Negeri 1 Batang Kapas. The kind of researchers used is a combination of Ex Post Facto and descriptive research, with a quantitative approach. The data is generated using the information in the form of questionnaire, interviews, and learning results test. The  obtained data was analyzed by using descriptive and simple linear regression. Based on data analysis obtained: 1) The result of student learning interest assessments have an average of 62,38 in the category of interest. 2) Student’s learning results show the average student’s value is 52,78 with the highest value is 100 and the lowest value is 2 with deviation standard 31,777. 3) The analysis of interest and the learning result indicate that the student’s interest related to learning result of student of UPT SMP Negeri 1 Batang Kapas with the t count > t table (4,173 > 2,001) at a 5% level of significance,  indicating that the student’s interest variable had a significant relationship to the learning result. It also indicates that the higher the student's interest, the better the results of learning acquired by the student of class VII in UPT SMP Negeri 1 Batang kapas. Keyword – Interest, results in learning